2020
DOI: 10.4251/wjgo.v12.i7.782
|View full text |Cite
|
Sign up to set email alerts
|

Role of prophylactic hyperthermic intraperitoneal chemotherapy in patients with locally advanced gastric cancer

Abstract: BACKGROUND Gastric cancer is the second most common malignant tumor in China, ranking third among all malignant tumor mortality rates. Hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to increase significantly the effectiveness of intraperitoneal chemotherapeutic drugs, prolong the action time of these drugs on intraperitoneal tumor cells, and enhance their diffusion in tumor tissues. HIPEC may be one of the best choices for the eradication of residual cancer cells in the abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…A growing number of studies have shown that intraoperative or postoperative intraperitoneal chemotherapy can dramatically reduce the risk of postoperative peritoneal recurrence and increase the survival rate ( 5 , 6 ). In recent years, intraoperative prophylactic intraperitoneal chemotherapy gradually becomes applied in clinical practice ( 7 , 8 ). The randomized controlled trial using hyperthermic intraperitoneal chemotherapy (HIPEC) in patients at risk for peritoneal metastases of gastric cancer was reported by Yonemura et al.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that intraoperative or postoperative intraperitoneal chemotherapy can dramatically reduce the risk of postoperative peritoneal recurrence and increase the survival rate ( 5 , 6 ). In recent years, intraoperative prophylactic intraperitoneal chemotherapy gradually becomes applied in clinical practice ( 7 , 8 ). The randomized controlled trial using hyperthermic intraperitoneal chemotherapy (HIPEC) in patients at risk for peritoneal metastases of gastric cancer was reported by Yonemura et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited studies are found in the medical literature that was done to assess the prophylactic role of HIPEC in the prevention and control of peritoneal metastasis of gastrointestinal origin. Xie et al (2020[ 34 ]) had done a non-RCT in China to study the role of prophylactic HIPEC after radical gastrectomy in patients with locally advanced gastric cancer. With results showing peritoneal recurrence rates of 4 % in the HIPEC group, the authors concluded that prophylactic HIPEC is beneficial in reducing the peritoneal recurrence rate and improving overall survival in patients with locally advanced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies (2RCTs, 3NRCTs), 415 patients were reported overall 1-year survival [25,26,28,34,43]. Analyzing under the random effects model, the overall heterogeneity (I 2 =62%) is acceptable.…”
Section: Meta-analysis and Synthesismentioning
confidence: 98%
“…Among them, 9 studies were published after 2015. Most of the included studies are from Asia, including 8 from mainland China [23][24][25][26][27][28][29] and Taiwan ROC [30], 10 from Japan [31][32][33][34][35][36][37][38][39] and Korea [40]. The other three studies are from Belarus [41], Italy [42], Ukraine [43], and Brazil [44]…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation